UPAYA MENINGKATKAN PRESTASI BELAJAR SOSIOLOGI TENTANG STRATEGI PEMBERDAYAAN KOMUNITAS LOKAL DENGANMENGEDEPANKAN NILAI-NILAI KEARIFAN LOKAL DI TENGAH –TENGAH PENGARUH GLOBALISASI PADA SISWA KELAS XII IPS 1 DI SMAN 1 RAMBAH MELALUI STRATEGI TEBAK KATA - Rn - Sunariyah (STKIP ROKANIA, 2020)
This Classroom Action Research (PTK) is an effort to improve learning achievement in sociology subjects in the strategy of empowering local communities by prioritizing local wisdom values ​​in the midst of the effects of globalization on class XII IPS.1 SMAN 1 RAMBAH school year 2019/2020. . The purpose of this research is to describe the improvement of sociology learning achievement about local community empowerment strategies by promoting local wisdom. There is also a method used in this research is to use a classroom action research design (Clasroom Action Research). The results showed that the use of Guess the Words learning technique in sociology lessons in the material of local community empowerment strategies by prioritizing local wisdom values ​​in the midst of the effects of globalization, students of class XII IPS.1 SMAN 1 Rambah in the 2019/2020 academic year, can improve Sociology learning achievement, this can be seen in the increase in student achievement.